Hubungan Academic Burnout Dengan Academic Procrastination Pada Mahasiswa Keperawatan Politeknik Negeri Subang - Ananda Lianti Jenal; Irwan Agustian; M. Iqbal Angga Kusuma (Jurnal Keperawatan Dan Kesehatan Holistik, 2026)
Nursing students face high academic demands, such as a heavy course load, clinical practice, and complex academic requirements. These conditions can trigger academic procrastination and academic burnout, which are characterized by emotional exhaustion, a cynical attitude toward assignments, and a decline in personal achievement. These two conditions are believed to be interrelated and to influence students’ academic performance. This study aims to determine the relationship between academic burnout and academic procrastination among nursing students at the Subang State Polytechnic. This study employed a quantitative design with a cross-sectional approach, involving a population of 365 active students in the D-III Nursing Program at the Subang State Polytechnic. The sample consisted of 196 students selected using stratified random sampling. The research instruments used were the School Burnout Inventory (SBI) and the Academic Procrastination Scale-Short Form (APS-S). Data analysis was performed using the Spearman rank correlation test. There was a significant positive relationship between academic burnout and academic procrastination (r = 0.408; p < 0.001) with a moderate strength of association. The higher the level of academic burnout, the higher the level of academic procrastination. Students are encouraged to improve their stress management skills, develop adaptive coping strategies, practice good time management, and utilize social support to reduce academic pressure. The findings of this study have implications for nursing education institutions to develop academic burnout prevention programs as a means of reducing academic procrastination among students.